Metastasectomy versus radiation of secondary sites in stage IV breast cancer: Analysis from a national cancer registry. (December 2021) - Bilani, Nadeem; Yaghi, Marita; Main, Olivia; Naik, Mihir; Jabbal, Iktej; Rivera, Carlos; Elson, Leah; Liang, Hong; Saravia, Diana; Nahleh, Zeina
Abstract: Purpose: Locoregional therapy at primary or secondary sites in breast cancer may be associated with improved survival as compared to systemic therapy alone. We explored the sociodemographic and clinicopathologic factors associated with the use of radiation versus surgical resection of metastatic sites (metastasectomy) in patients with de novo stage IV breast cancer, followed by the associated overall survival. Methods: We sampled the National Cancer Database for patients with de novo stage IV breast cancer, (2010–2017) and described cohort's characteristics using univariate analyses. We identified 5 subgroups based on malignant site involvement: 1. Bone only, 2. Brain only, 3. Liver only, 4. Lung only, and 5. Metastasis involving >1 site. Kaplan-Meier modeling with log-rank testing and multivariate Cox Regression analysis were used to explore differences in overall survival between those that received radiation at secondary sites and those that underwent metastasectomy. Results: N = 22, 749patients were included in this analysis. Radiation (81.2%) was used more commonly than metastasectomy (28.8%). Metastasectomy was associated with better median overall survival across all 5 cohorts (p < .001), with the survival benefit being the most pronounced with lung only (OS: 56.9 months; HR 0.8, 95% CI 0.7–0.9, p = .032), or liver only (OS: 41.6 months; HR: 0.9; 95% CI: 0.7–1.1, p < .001) metastasis. Conclusion: Metastasectomy in patients with de novo stage IV breast cancer may be associated with improved overall survival as compared to radiation of secondary lesions, particularly in those with only liver or lung involvement. Prospective randomized controlled trials investigating surgical resection of metastatic sites in patients with breast cancer are warranted. Highlights: Metastasectomy in Stage IV breast cancer leads to improved survival regardless of organ involvement and number of lesions. The survival benefit of metastasectomy is most apparent when the breast cancer metastasis involves the liver or the lung. Radiation and metastasectomy should be considered for treatment of secondary breast cancer lesions in clinical practice.